Analysis of mitochondrial DNA polymorphism in the atpA region and design of simple sequence repeat and sequence characterized amplified region markers for distinguishing AD1, CMS‐D2 and CMS‐D8 cytoplasms in cotton (Gossypium spp.). (11th March 2022) - Ding, Jiaqi; Sun, Guoqing; Li, Quanjiang; Wang, Jing; Li, Caihua; Zhang, Lanlan; Meng, Zhigang; Zhou, Tao; Shi, Ji; Ji, Wei; Liu, Jian; Zhang, Xiao; et al.
Abstract: Previous studies showed that there were differences among AD1, CMS‐D2 and CMS‐D8 in the atpA gene region of the mitochondrial genome of cotton, but their detailed DNA sequence differences were unclear. RFLP analysis here showed that the mitochondrial atpA gene existed as two copies of different lengths in each line. Inverse polymerase chain reaction (PCR) and sequencing results revealed that one copy contained an intact atpA gene, while the other copy contained a 3′‐truncated version. In the 3′ flanking region of the intact atpA gene, an simple sequence repeat (SSR) locus was found, with the sequences in AD1, CMS‐D2, and CMS‐D8 being (TAA)7 (TA)6, (TAA)3 (TA)2, and (TAA)4 (TA)3, respectively. In the 3′ flanking region of the 3′‐truncated copy, a 515‐bp specific chimeric fragment was found in AD1, while a 555‐bp specific chimeric fragment was found in the two CMS lines, and CMS‐D2 possessed three single‐nucleotide polymorphism (SNP) sites compared with CMS‐D8. Furthermore, AD1‐specific, CMS‐D2‐specific and CMS‐D8‐specific sequence characterized amplified region (SCAR) markers were developed to distinguish the three cytoplasms. This study will be useful for distinguishing genotypes in breeding practices and evolutionary studies of cotton.